6-KLASS OQÍWSHÍLARÍNA TÁBIYIY PÁNLERDI OQÍTÍWDA QOLLANÍLATUǴÍN INNOVACIYALÍQ METODLAR - Gaypova, Roza Tursinbaevna; Kallibekova, Venera (SCIENCE and SOCIETY, 2026)
The article scientifically and theoretically illuminates the effectiveness of innovative pedagogical methods, information and communication technologies, the STEAM approach, project-based learning, and practical exercises used in teaching 6th-grade physical geography lessons. The role of interactive methods in activating students’ cognitive activity is analyzed. The article has practical and methodological significance for geography teachers in general secondary education institutions.